2003
DOI: 10.1128/iai.71.5.2365-2372.2003
|View full text |Cite
|
Sign up to set email alerts
|

Invasion and Killing of Human Endothelial Cells by Viridans Group Streptococci

Abstract: Colonization of the cardiovascular endothelium by viridans group streptococci can result in infective endocarditis and possibly atherosclerosis; however, the mechanisms of pathogenesis are poorly understood. We investigated the ability of selected oral streptococci to infect monolayers of human umbilical vein endothelial cells (HUVEC) in 50% human plasma and to produce cytotoxicity. Planktonic Streptococcus gordonii CH1 killed HUVEC over a 5-h period by peroxidogenesis (alpha-hemolysin) and by acidogenesis but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 60 publications
1
56
0
2
Order By: Relevance
“…Invasion of host cells represents a bacterial mechanism to evade innate and adaptative immunity and to persist in host cells and tissues (21)(22). The invasion ability of human oral cells has been described for oral bacterial species as viridans streptococci (23)(24), Porphyromonas gingiva/is and Aggregatibacter actnomycetemcomitans, causative agents of periodontitis (25)(26). Concerning S. mutans, it is able to gain access to the bloodstream, leading to transient bacteraemia (27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Invasion of host cells represents a bacterial mechanism to evade innate and adaptative immunity and to persist in host cells and tissues (21)(22). The invasion ability of human oral cells has been described for oral bacterial species as viridans streptococci (23)(24), Porphyromonas gingiva/is and Aggregatibacter actnomycetemcomitans, causative agents of periodontitis (25)(26). Concerning S. mutans, it is able to gain access to the bloodstream, leading to transient bacteraemia (27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the glucosyltransferase enzyme is an important virulence factor in systemic infections due to its ability to synthesize capsule-like extracellular polysaccharide (25) and to enhance adhesion to and invasion and killing of endothelial cells in vitro (46,52). In this study, 39% of the 107 isolates from blood possessed the gtf gene.…”
Section: Discussionmentioning
confidence: 99%
“…The shortcoming of this method is that it is unable to identify other species. However, it has been suggested that the glucosyltransferase enzyme (GTF) is an important virulence factor in systemic infections, being responsible for biosynthesis of the capsule-like extracellular polysaccharide (25) and for adhesion to and invasion and killing of cultured human umbilical endothelial cells (46,52). For this reason, it was interesting to investigate the proportion of streptococci from cases of endocarditis and septicemia that carry the gtf gene.…”
mentioning
confidence: 99%
“…COX-2 Degradation Studies-Cells cultured for 12 h on gelatincoated plates were washed twice with PBS, detached by trypsin treatment, and immediately exposed to different inhibitors: protease inhibitor mixture at 1:1000 dilution (33) Cell Adhesion Assays-Maxisorp II Nunc enzyme-linked immunosorbent assay plates (Roskilde, Denmark) were coated with 10 g/ml laminin, collagen I, fibronectin, or vitronectin overnight at 4°C and blocked with BSA for 2 h at room temperature. Assays were done as previously described (32).…”
Section: Methodsmentioning
confidence: 99%